IDENTIFIKASI VISUAL BATUAN PAF DAN NAF STUDI KASUS DI PT ARUTMIN INDONESIA ASAM ASAM - Wahyu Gilang Nugraha; Yudi Firmanul Arifin; Idiannor Mahyudin; Wahyuni Ilham (EnviroScienteae, 2016)
The research location is in Asam-Asam PT Arutmin Indonesia, located in District Jorong, Tanah Laut, Kalimantan Selatan. This study aims to determine the relationship of visual rock with PAF and NAF rock properties based on the distribution pattern, volume, and utilization. Visual identification that shows the strong correlation of PAF on the grain size of silt, color dark gray lithology, and lithologic silt. a strong correlation was also found on NAF rock with a grain size of clay, fine sand, very fine sand. In the color white rock medium, medium gray, light gray. obtained a volume of PAF: 208 309 329 BCM, NAF = 200 764 182 BCM volume, so the volume of NAF to be taken can coat 3,5 meters disposal.